Chiefdom Madinah salah paham negara Islam - Aziz, Abdul (Kerja sama Pustaka Alvabet dan Lembaga Kajian Islam & Perdamaian, 2011)
Role of Islam in the state formation in Medina, Saudi Arabia under Prophet Muhammad, and idea to establish Islamic state in Indonesia.